SOCIAL BEHAVIOR PARADIGM ‎ AND SOCIAL EXCHANGE BEHAVIORISTIC APPROACH - Aspandi Aspandi (Institute of Research and Community Service, Institute of Pesantren Kiyai Haji Abdul Chalim, 2020)
The sociology paradigm gave birth to a variety of paradigms including; the paradigm of social facts, the paradigm of social definition and the paradigm of social behavior. In contrast to the two previous paradigms, the paradigm of social behavior focuses its discussion on the relationship of individuals and their environment in social interactions and their repetition. The paradigm of social behavior was born as a critique of the paradigm of social facts and social definitions as a perspective that is mystical, cannot be explained rationally and is considered unscientific. The paradigm of social behavior develops in